Manipulating and probing the polarisation of a methyl tunnelling system by field-cycling NMR - Zhang, Bo; Abu-Khumra, Sabah; Aibout, Abdellah; Horsewill, Anthony J. (AIP Publishing, 2017)
In NMR the polarisation of the Zeeman system may be routinely probed and manipulated by applying resonant rf pulses. As with spin-½ nuclei, at low temperature the quantum tunnelling states of a methyl rotor are characterised by two energy levels and it is interesting to consider how these tunnelling states might be probed and manipulated in an analogous way to nuclear spins in NMR. In this paper experimental procedures based on magnetic field-cycling NMR are described where, by irradiating methyl tunnelling sidebands, the polarisations of the methyl tunnelling systems are measured and manipulated in a prescribed fashion. At the heart of the technique is a phenomenon that is closely analogous to dynamic nuclear polarisation and the solid effect where forbidden transitions mediate polarisation transfer between ¹H Zeeman and methyl tunnelling systems. Depending on the irradiated sideband, both positive and negative polarisations of the tunnelling system are achieved, the latter corresponding to population inversion and negative tunnelling temperatures. The transition mechanics are investigated through a series of experiments and a theoretical model is presented that provides good quantitative agreement.